The Impact of Appropriate Interpersonal Touch (AIT) via Handshake on Perceived Credibility of Interpreter and Message. Issue 2 (November 2018) - Shortt, Mickey; Laird, Shelby Gull; Darville, Ray; Williams, Pat Stephens
The role of interpersonal touch has been studied in communication fields, demonstrating a handshake or other form of appropriate interpersonal touch (AIT) has rendered favorable results in rapport building with an audience as well as developing audience comfort and receptivity to messaging. This study aimed to determine if the use of a handshake prior to interpretive programming would increase the positivity of perception of a visitor toward interpreters and/or the message shared by interpreters. Four interpreters gave both control and test interpretive programs, with 404 participants completing surveys at the site for a period of about one month. The interpreters were then asked to reflect on their practice at the end of the study. The research also discusses viewpoints of professionals in the field of interpretation about the current use and perception of touch. Trough three angles, the research demonstrated that AIT positively affects a visitor's perception of the interpreter and the message shared. The research also highlights and discusses boundaries in the use of touch and next steps toward researching AIT's role in the field of interpretation.